Speech Outcome in Cleft Palate Patients After Soft Palatoplasty (Stage 1) in Two-Stage Palatoplasty Technique: A Review of Two Cases - Sutrisno, Eddy H; Wahyuni, Luh K.; Lilisantosa, Kartika (Jurnal Plastik Rekonstruksi, 2012)
Background: The challenge in palatoplasty is no longer a successful closure of the cleft palate but an optimal speech outcome without compromising maxillofacial growth. On the contrary, repairing cleft palate as soon as possible is recommended to improve speech. The surgeon proposed two-stage palatoplasty in early aged, range between 4 to 30 months. The delayed hard palate closure started approximately between the age of three years and one year after soft palatoplasty to avoid temporary retracted oral articulation of certain consonant. Patient and Methods: 11-months old and 9-months old patients with non-syndromic unilateral cleft lip and palate had undergone soft palatoplasty. Speech was examined as a perceptual assessment, using protocol in Craniomaxillofacial Center Cipto Mangunkusumo Hospital, in the age of 29 months by an experienced speech pathologist. Result: Patient 1 has mild hypernasality, adequate velopharyngeal competence, normal articulation pattern, phonation and speech intelligibility. Patient 2 has misarticulation pattern,which are omission or weak consonants, substitution of pharyngeal stop, mild to moderate hypernasality, mild impairment in speech intelligibility, and inadequate velopharyngeal competence.Summary: Speech outcome is influenced by intense speech practicing done by their parents. The patient can work on the misarticulation. We need further study to know the result of speech outcome in two stage palatoplasty.